Strategic Alignment of Value Co Creation Models: A Comparative Analysis of Servitized Manufacturing and Pure Service Firms - Jakfar (Indonesian Scientific Publication, 2024)
This study investigates the comparative dynamics of value co-creation models in servitized manufacturing firms and pure service firms. The research identifies sector-specific strategies that enhance innovation and competitiveness, with particular attention to governance, ecosystem engagement, and brand management practices. A mixed-methods approach was employed, combining secondary data analysis with a comparative framework grounded in Service-Dominant Logic (SDL) and the DART model. Four manufacturing co-creation models were evaluated against practices in service firms using metrics such as innovation velocity, customer retention, and revenue contribution. The findings show that in manufacturing, the Double High and Servitization Leading models deliver stronger performance when supported by ecosystem engagement and effective governance. Service firms, by contrast, thrive through broader networks, agility, and continuous interaction, enabling rapid adaptation and personalization. Across both sectors, governance mechanisms and brand coherence are critical to sustaining trust, efficiency, and alignment with customer expectations. The study concludes that co-creation is a sector-dependent strategic discipline. Tailored strategies, aligned with governance and ecosystem realities, can generate sustainable competitive advantages. Future research should examine how emerging technologies, cross-sector collaborations, and cultural contexts shape the evolution of co-creation models.